Livelihood development for women with vision impairments in the informal sector in Ghana - Agbettor, Elizabeth Ladjer Bibi (Department of Health and Rehabilitation Sciences, 2022)
Livelihood development and participation of women in the informal sector have been recognised as a key factor for social and economic liberation. When women, especially women with vision impairments, participate in livelihood, they reap the benefits of a stable income source, a better standard of living, good physical and emotional health, self-identity, self-assertiveness, and positive social status. However, there is a limited body of scientific knowledge on women with vision impairments' livelihood development and participation experience in the informal sector in the Ghanaian context. To address this knowledge gap, a qualitative case study was conducted to explore how livelihood development opportunities offered by the Ghana Blind Union (GBU) and its partners achieve self-employment and economic empowerment of women with VI in Ghana. The broad research question was: 1) How do livelihood development strategies by GBU and partners provide opportunities for self-employment and economic empowerment of women with vision impairments in Ghana? The four sub research questions were: 1) What are the existing livelihood skills development strategies of women with vision impairments in Ghana? 2) How are the livelihood skills provided for women with vision impairments? 3) What opportunities for selfemployment have women with vision impairments accessed (or not) 4) Why are livelihood skills development strategies of women with vision impairments enabling or hindering their selfemployment and economic empowerment? The study was guided by theoretical perspectives from the Social Disability Model, Sen's Capability Approach (CA), and the Community-Based Rehabilitation (CBR) guidelines. The Social Disability Model was used to look at the livelihood development and participation of the women from social and cultural perspectives. The CA was used to examine livelihood development in the context of capabilities and the influence of social, political, and physical environments on the women's livelihood activities. The CBR guidelines were used to explore livelihood service provision and multi-sectoral involvement in the context of the study. The data was collected from fourteen women with vision impairments and six service providers using individual interviews, focus group discussions, document review and field notes. The data was analysed thematically and three themes emerged: Our cloudy path: Engaging in livelihood, We are deprived because we are blind, and Transitioning from zero to hero. It was established that skills that will enable women with vision impairments' livelihood are available but the women gamble with skills acquisition because of the nature of the service design and implementation. It was also evident that non-implementation of policies and social protection programmes deprive women with vision impairments of livelihoods. Further, negative societal attitudes and misconceptions about blindness compound the burdens of women with vision impairments in livelihood. However, when women with vision impairments engage in livelihood activities and earn regular income, their social status is enhanced and they serve as peer educators and mentors to other women with vision impairments. It was concluded that the livelihood path of women with vision impairments is cloudy. The livelihood path of the women presented complicated and unique challenges, but with resilience, the women were able to overcome the challenges and serve as social assets to their families, the GBU, and the entire social collective. This study provides critical new knowledge on the experience of women with vision impairments in terms of livelihood participation in the informal sector within the Ghanaian context. The new knowledge adds to the current limited evidence in the literature on livelihood participation of women with vision impairment in the informal sector. The study also provided an inclusive livelihood development framework to guide livelihood development practice in Ghana.